South Korean unmarried single women's images in the 2000s through major South Korean newspapers - Dung, Nguyen Thi Hanh (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2023)
South Korean women's images mostly connect with the ideal women's images of “good wives, wise mothers”. However, the number of single women in South Korea population has been increasing significantly in recent years. Various media outlets such as television and newspapers have been mentioning and discussing the lifestyles and mindsets of Korean single women, often using hot keywords such as "Gold Miss", "unmarried single women (Bihon)", and "single women (Mihon)" in both positive and negative contexts. This study aims to explore the most popular and representative characteristics of South Korean single women and figure out the transition of single women's images in the 2000s since the Asian financial crisis in South Korea. Based on literature reviews and newspaper reference sources, this research also aims to find out what people think about the most popular images of South Korean single women nowadays, then summarizes the similarities and differences in the popular images of South Korean unmarried single women described by Korean newspapers's discourse and existing literature reviews.